The role of biochar on greenhouse gas offsets, improvement of soil attributes and nutrient use efficiency in tropical soils - Abbruzzini, Thalita Fernanda (2015)
The solid product of pyrolysis, called \"biochar\" (BC) in the context of improving soil properties as part of agronomic or environmental management, also got into focus as a climate mitigation strategy. The researcher investigated the effects of BC on soil attributes, nitrogen (N) use and GHG emissions. In Chapter 1 the origin of BC was commented. In Chapter 2, BC from sugarcane straw was characterized, and its priming on native SC was evaluated with the treatments: (T1) Soil; (T2) BC; (T3) Soil + BC 10 Mg ha-1; (T4) Soil + BC 20 Mg ha-1; and (T5) Soil + BC 50 Mg ha-1. In Chapter 3, it was evaluated the combination of BC, filter cake (F) and vinasse (V), in relation to soil attributes and carbon dioxide (CO2), methane (CH4) and nitrous oxide (N2O) emissions. The treatments were: (T1) Soil + FC + V; (T2) Soil + FC + V + BC 10 Mg ha-1; (T3) Soil + FC + V + BC 20 Mg ha-1; and (T4) Soil + FC + V + BC 50 Mg ha-1. In Chapter 4, the nitrogen (N) use efficiency was investigated in a pot trial under wheat using NH4[15N]O3 and rates of BC, with the treatments: (T1) Soil, with N, no BC; (T2) Soil, with N, BC 10 Mg ha-1; (T3) Soil, with N, BC 20 Mg ha-1; and (T4) Soil, with N, BC 50 Mg ha-1. BC had C and N contents higher compared to the feedstock. Total K, Mg and P also increased. The lowest CO2 fluxes were for BC, and CO2 from soil and soil + BC did not differ. The highest CO2 - C4 was in the first day, and there were no differences in the CO2 - C3. The BC presents characteristics to improve soil attributes. BC stability is an opportunity to reduce CO2 emissions. In Chapter 3, soil pH, P and base contents increased and Al3+ decreased with BC to sandy soil. Impacts of BC on the CEC were higher in sandy soil. Mineral N decreased with BC. Cumulative CO2 in T1 were higher in sandy and clayey soils than the control. T2 and T3 in sandy soil increased CO2 emissions, but T4 did not differ from T1. BC reduced N2O emissions from sandy and clayey soils relative to T1. BC with FC and V affected pH, CEC, P and base contents. However, those effects were higher in sandy soil. The BC supressed N2O from V and FC. In Chapter 4, BC decreased N2O from N fertilization compared to only N fertilizer. T4 had higher tillering and grain yield. Also, T2 to T4 had higher 100-grain weight and shoot. T3 and T4 had the highest N in grains. The application of BC to soil improves N availability and use efficiency, enhances grain yields and reduces N2O from N fertilization. This study opened encouraging perspectives to the evaluation of sugarcane straw BC to improve soil quality and mitigate GHG emissions.